Is sexual abuse a part of war? A 4-year retrospective study on cases of sexual abuse at the Kenyatta National Hospital, Kenya - Mary W. Kuria (Journal of Public Health in Africa, 2013)
The harmful effects of sexual abuse are long lasting. Sexual abuse when associated with violence is likely to impact negatively on the life of the victim. Anecdotal reports indicate that there was an increase in the number of cases of sexual violence following the 2007 post election conflict and violence in Kenya. Although such increases in sexual abuse are common during war or conflict periods the above reports have not been confirmed through research evidence. The purpose of the current study is to establish the trend in numbers of reported cases of sexual abuse at Kenyatta National Hospital over a 4-year period (2006-2009). Data on sexually abused persons for the year 2006-2009 was retrieved from the hospitals record. A researcher designed questionnaire was used to collect relevant data from the completed Post Rape Care (PRC) form. The PRC-Ministry of Health no. 363 (MOH363) form is mandatorily completed by the physician attending the sexually abused patient. There was an increase in the number of cases of sexual abuse reported in 2007 election year in Kenya, with a statistically significant increase in the sexually abused male cases. Sexual crime is more prevalent when there is war or conflict.